EFFECT OF ACOUSTIC-GRAVITY WAVE OF THE LITHOSPHERIC ORIGIN ON THE IONOSPHERIC F REGION BEFORE EARTHQUAKES - Rapoport Yu.G.; Gotynyan O.E.; Ivchenko V.M.; Kozak L.V.; Parrot M. (My University, 2004)
An accurate 3D numerical model of the acoustic-gravity wave (AGW) excitation before an earthquake is proposed and linear plasma response in F region of the ionosphere is studied. It is shown that “reactive modes” of AGW are important to model adequately the excitation and propagation of waves belonging to both gravity wave (GW) and acoustic wave (AW) branches of AGW. Dependence of the ionospheric response (namely, relative change in electron concentration) on temporal (period) and spatial (shape) properties of the lithospheric gas AGW source is emphasized. It is shown that the peak value in spatial distribution of electron concentration relative change for the elongated 2D source has a maximum for AGW period, τ which increases with increasing a source length. Maximal ionospheric response corresponds to AGW with a typical period of the order of 1 h. Both this period and absolute value of relative change in electron concentration of the ionospheric F-layer are coincident by the order of value with the reported data of observations before earthquakes. Relative change in electron concentration reaches a maximal value for the angle between geomagnetic field and vertical direction of the order of 80°. Wind can increase asymmetry in the spatial distribution of relative change in electron concentration and at the same time increase peak value of this distribution. In accordance with present calculations, possible turbulent effects (namely turbulent heating and change of turbulent heat conduction coefficient) takes place at altitude ∼96 km in the region with radius of the order of 100 km. This region coincides with those where temperature increased before earthquakes, in accordance with the data of UARS satellite observations.